Medium-entropy copper alloy and preparation method and application thereof
By introducing Co elements into the copper manganese nickel-tin entropy copper alloy, and carrying out solid solution treatment and aging treatment, the problem of discontinuous precipitation phase formation in the alloy is solved, significantly improving its mechanical properties and wear resistance, and expanding its application range.
Patent Information
- Application Number
- CN202411712921.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
In the smelting and casting process of copper manganese nickel-tin, the tin element component segregation is prone to occur, which affects the composition uniformity and mechanical properties of the alloy. The microalloyization method has no obvious effect on suppressing the formation of discontinuous precipitation phases, making it difficult to improve its mechanical properties and wear resistance.
By introducing Co elements with a higher melting point and performing solid solution treatment and aging treatment under specific heat treatment conditions, the formation of discontinuous precipitated phases is suppressed, and the H-L12 phase is uniformly distributed, thereby improving the mechanical properties of the alloy.
It effectively inhibits the formation of thick lamellar discontinuous precipitation phases in medium-entropy copper alloys, improves its hardness, strength, toughness and wear resistance, and expands its application range.
Smart Images

Figure CN119530610A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medium-entropy alloys, and in particular relates to a medium-entropy copper alloy and a preparation method and application thereof. Background Art
[0002] Copper alloys have moderate hardness, good latent properties and compliance, as well as low friction coefficient and good wear resistance. They are widely used in mechanical engineering as sliding bearings, bushings, bushings, slides, turbines and gears. Medium-entropy copper alloys are a new type of material developed in recent years based on conventional copper alloys. They inherit the excellent properties of conventional copper alloys and have high strength, high plasticity and toughness, as well as better wear resistance and corrosion resistance. They are expected to become a new generation of wear-resistant self-lubricating materials used in aviation, aerospace and marine engineering.
[0003] The copper-manganese-nickel-tin medium-entropy copper alloy is the most typical type among them. This alloy has good high temperature resistance, high strength and good wear resistance, and has great application prospects under high temperature friction conditions. This alloy is currently mainly prepared by melting and casting methods. However, due to the large liquid-solid interval between the components of the copper-manganese-nickel-tin alloy during the melting and casting process, the liquid alloy is prone to component segregation of the tin element during the solidification process, which affects the composition uniformity of the alloy and further improvement of the mechanical properties. In addition, in addition to the micro-segregation between dendrites formed during the solidification process, the coarse lamellar discontinuous precipitate phase formed in the later stage of aging will greatly deteriorate the strength, toughness and plasticity of the alloy.
[0004] The microalloying method has a good effect on inhibiting the precipitation of coarse lamellar discontinuous structures in conventional copper-nickel-tin alloys. However, for copper-manganese-nickel-tin medium-entropy alloys, due to the lattice distortion effect and slow diffusion effect caused by the high concentration of multiple components mixed, the effect of microalloying on inhibiting the precipitation of discontinuous precipitates in copper-manganese-nickel-tin medium-entropy copper alloys is not obvious, making it difficult to improve its mechanical properties and wear resistance through microalloying. At present, how to further improve the mechanical properties and wear resistance of copper-manganese-nickel-tin medium-entropy copper alloys is a key issue that needs to be solved urgently. Summary of the invention
[0005] In view of this, the present invention provides a medium-entropy copper alloy and a preparation method and application thereof. The present invention effectively inhibits the formation of coarse lamellar discontinuous precipitate phases in the copper-manganese-nickel-tin medium-entropy copper alloy, thereby improving its mechanical properties and tribological properties. The medium-entropy copper alloy provided by the present invention has high hardness, strength, toughness and wear resistance, greatly expanding its application range.
[0006] In order to solve the above technical problems, the present invention provides a medium entropy copper alloy, comprising the following elemental components in atomic percentage:
[0007]
[0008] Preferably, the microstructure of the medium entropy copper alloy includes A1 phase, B1 phase and H-L1 phase. 2 Mutually.
[0009] Preferably, the H-L1 2 The volume percentage of the phase is 5 to 18%.
[0010] The present invention also provides a method for preparing the medium-entropy copper alloy described in the above technical solution, comprising the following steps:
[0011] The materials are mixed according to the element ratio and then smelted, and the molten alloy obtained by smelting is cooled to obtain an ingot;
[0012] The ingot is subjected to solution treatment and aging treatment in sequence to obtain the medium-entropy copper alloy.
[0013] Preferably, the solution treatment is carried out at a temperature of 780 to 900° C. and for a time of 3 to 6 hours.
[0014] Preferably, the heating rate to the temperature required for the solution treatment is 10-12°C / min.
[0015] Preferably, the aging treatment is carried out at a temperature of 400 to 550° C. and for a time of 3 to 5 hours.
[0016] Preferably, the heating rate to the temperature required for the aging treatment is 5 to 12° C. / min.
[0017] Preferably, the smelting includes vacuum induction melting or suspension melting;
[0018] The smelting temperature is 1200-1550° C. and the smelting time is 10-30 minutes.
[0019] The present invention also provides the use of the medium-entropy copper alloy described in the above technical solution or the medium-entropy copper alloy prepared by the preparation method described in the above technical solution as a wear-resistant material.
[0020] The present invention provides a medium entropy copper alloy, comprising the following elemental components in atomic percentage: 43-47% Cu, 7-9% Mn, 6-8% Sn, 30-40% Ni and 0.1-10% Co. The present invention introduces a Co element with a relatively high melting point into the alloy, and its solubility in the solid solution is relatively small. Therefore, during the solidification or aging process of the alloy, the Co element will preferentially occupy the grain boundary or a position close to the grain boundary, hindering the diffusion of other alloy components, thereby inhibiting the formation and growth of discontinuous precipitation phases, thereby reducing the discontinuous precipitation phases, and making H-L1 2The phase is evenly and continuously distributed in the alloy matrix, thereby improving the mechanical properties of the medium-entropy copper alloy. The medium-entropy copper alloy provided by the present invention has uniform composition, stable structure, extremely high mechanical strength at room temperature, and good fracture toughness and wear resistance. It can meet the urgent needs of mining metallurgy, aerospace, automobile, energy and equipment manufacturing for advanced structural copper alloy materials, and has broad application and promotion prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Cu prepared in Example 1 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 XRD spectrum of medium entropy copper alloy;
[0022] Figure 2 The Cu prepared in Example 1 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 SEM image of medium entropy copper alloy;
[0023] Figure 3 The Cu prepared in Example 1 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 Compressive mechanical properties curve of medium entropy copper alloy;
[0024] Figure 4 The Cu prepared in Example 2 45 Mn 8 Ni 35 Sn 7 Co 5 XRD pattern of medium entropy copper alloy;
[0025] Figure 5 The Cu prepared in Example 2 45 Mn 8 Ni 35 Sn 7 Co 5 SEM image of medium entropy copper alloy;
[0026] Figure 6 The Cu prepared in Example 2 45 Mn 8 Ni 35 Sn 7 Co 5 Compressive mechanical properties curve of medium entropy copper alloy;
[0027] Figure 7 The Cu prepared in Example 3 45 Mn 8 Ni 30 Sn 7 Co 10 XRD spectrum of medium entropy copper alloy;
[0028] Figure 8 The Cu prepared in Example 3 45 Mn 8 Ni 30 Sn 7 Co 10 SEM image of medium entropy copper alloy;
[0029] Fig. 9 The Cu prepared in Example 3 45 Mn 8 Ni 30 Sn 7 Co 10 Compressive mechanical property curve of medium entropy copper alloy. DETAILED DESCRIPTION
[0030] The present invention provides a medium entropy copper alloy comprising the following elemental components in atomic percentage:
[0031]
[0032] In terms of atomic percentage, the medium entropy copper alloy provided by the present invention includes 43-47% Cu, which may be specifically 43%, 45% or 47%.
[0033] In terms of atomic percentage, the medium entropy copper alloy provided by the present invention includes 7-9% Mn, which may be specifically 7%, 8% or 9%.
[0034] In terms of atomic percentage, the medium entropy copper alloy provided by the present invention includes 6-8% Sn, which may be specifically 6%, 7% or 8%.
[0035] In terms of atomic percentage, the medium entropy copper alloy provided by the present invention includes 30-40% Ni, which may be specifically 30%, 32.5%, 35%, 37.5% or 40%.
[0036] In terms of atomic percentage, the medium entropy copper alloy provided by the present invention includes 0.1-10% Co, which may be specifically 0.5%, 1%, 2.5%, 5%, 7.5% or 10%.
[0037] In the present invention, the composition of the medium entropy copper alloy may be a chemical formula of Cu 45 Mn 8 Ni 40-x Sn 7 Co x, where x can range from 0.1 to 10, and can specifically be 0.5, 1, 2.5, 5 or 10.
[0038] In the present invention, the microstructure of the medium entropy copper alloy includes A1 phase, B1 phase and H-L1 phase. 2 Phase; the H-L1 2 The volume percentage of the phase can be 5-18%. In the present invention, the A1 phase is a solid solution mainly composed of copper, manganese and nickel elements; the A1 phase has many slip systems, low hardness and strength, and excellent plasticity; the B1 phase is a tin-rich phase, with high hardness, high strength, and poor toughness and plasticity; H-L1 2 The phase belongs to an ordered precipitation phase; the present invention reduces the discontinuous precipitation phase in the medium entropy copper alloy by introducing Co and under specific heat treatment conditions, so that H-L1 2 The phase is evenly and continuously distributed in the alloy matrix, and the mechanical properties of the medium-entropy copper alloy are improved under the joint action of various element components.
[0039] The present invention also provides a method for preparing the medium-entropy copper alloy described in the above technical solution, comprising the following steps:
[0040] The materials are mixed according to the element ratio and then smelted, and the molten alloy obtained by smelting is cooled to obtain an ingot;
[0041] The ingot is subjected to solution treatment and aging treatment in sequence to obtain the medium-entropy copper alloy.
[0042] The present invention mixes the materials according to the element ratio and then melts them, and the alloy melt obtained by melting is cooled to obtain an ingot. The present invention has no special requirements on the type of materials used to prepare the medium-entropy copper alloy, and conventional materials in the field can be used. In the embodiment of the present invention, metal powder is selected as the material. As a specific embodiment of the present invention, the impurity content of the material can be less than 0.1wt%.
[0043] As a specific embodiment of the present invention, the smelting process may also include: ultrasonic cleaning and drying the materials respectively; the ultrasonic power may be 350-370W, specifically 350W, 360W or 370W, and the ultrasonic time may be 20-25min; the detergent for ultrasonic cleaning may be anhydrous ethanol; the drying temperature may be 75-80°C. The present invention has no special limitation on the drying time, as long as the solvent on the surface of the material can be removed.
[0044] As a specific embodiment of the present invention, the smelting may include vacuum induction melting or suspension melting; the smelting temperature may be 1200-1550°C, specifically 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C or 1550°C; the smelting time may be 10-30min, specifically 10min, 15min, 20min, 25min or 30min. As a specific embodiment of the present invention, the materials may be sequentially placed in a graphite crucible for smelting in the order of their melting points from low to high; the present invention limits the order of stacking materials to reduce splashing. As a specific embodiment of the present invention, the smelting may be carried out in a protective atmosphere, which may include argon or nitrogen; the furnace body may be evacuated before the protective atmosphere is introduced. As a specific embodiment of the present invention, the smelting may further include: refining the molten metal after smelting; the refining temperature may be 1400-1550°C, specifically 1400°C, 1450°C, 1500°C or 1550°C; the refining time may be 10-20min, specifically 10min, 15min or 20min.
[0045] As a specific embodiment of the present invention, the temperature after cooling can be room temperature, and the temperature of the room temperature can be 20-35° C. The present invention has no special limitation on the cooling method, and a conventional cooling method in the art can be used.
[0046] After obtaining the ingot, the present invention sequentially performs a solution treatment and an aging treatment on the ingot to obtain the medium entropy copper alloy. As a specific embodiment of the present invention, the temperature of the solution treatment can be 780 to 900°C, specifically 780°C, 800°C, 850°C or 900°C; the heating rate to the required temperature of the solution treatment can be 10 to 12°C / min, specifically 10°C / min, 11°C / min or 12°C / min; the holding time of the solution treatment can be 3 to 6h, specifically 3h, 4h, 5h or 6h.
[0047] As a specific embodiment of the present invention, the solution treatment can be carried out in an air atmosphere, a vacuum or an inert atmosphere; the solution treatment can be carried out in a heating furnace; the heating furnace can include a muffle furnace, a resistance furnace, a natural gas furnace, a carbon tube furnace, a vacuum heating furnace or an atmosphere heating furnace.
[0048] As a specific embodiment of the present invention, the solution treatment may also include: taking out the alloy after the solution treatment and placing it in room temperature water for quenching and then drying; the temperature of the room temperature water can be 10-30°C; the temperature of the drying can be 80-85°C, and the drying time can be 25-30 minutes.
[0049] As a specific embodiment of the present invention, the temperature of the aging treatment can be 400-550°C, specifically 400°C, 450°C, 500°C or 550°C; the heating rate to the required temperature of the aging treatment can be 5-12°C / min, specifically 5°C / min, 10°C / min or 12°C / min; the holding time of the aging treatment can be 3-5h, specifically 3h, 4h or 5h.
[0050] As a specific embodiment of the present invention, the aging treatment can be carried out in an air atmosphere, a vacuum or an inert atmosphere; the aging treatment can be carried out in a heating furnace; the heating furnace can include a muffle furnace, a resistance furnace, a natural gas furnace, a carbon tube furnace, a vacuum heating furnace or an atmosphere heating furnace.
[0051] As a specific embodiment of the present invention, the aging treatment may further include: cooling the alloy after the aging treatment to room temperature; the cooling method may be furnace cooling; the room temperature may be 20-35° C. As a specific embodiment of the present invention, mechanical cutting, cleaning and grinding may be performed in sequence after the alloy after the aging treatment is cooled to room temperature.
[0052] The present invention introduces the Co element into the medium-entropy copper alloy. The mixing enthalpy between Co and Cu, Mn, Ni and Sn elements is relatively high, and it is not easy to form complex phases such as intermetallic compounds. After solution treatment, it can be well dissolved in the matrix. In this process, in order to make the discontinuous precipitation phase fully dissolved into the matrix phase to create conditions for subsequent aging strengthening and prevent excessive growth of grains at high temperatures, a temperature range of 780 to 900 ° C is selected for solution treatment; the aging treatment temperature range is set to 400 to 550 ° C. This temperature range is conducive to triggering the diffusion-type precipitation reaction of the supersaturated solid solution and promoting aging strengthening. The Co element not only has a high melting point and weak chemical interaction with other components, but also has a small solubility in the solid solution. During the aging process, the Co element will preferentially occupy the nucleation position of discontinuous phases such as grain boundaries, which can significantly delay the nucleation and growth rate of the discontinuous precipitation phase, thereby improving the high-temperature aging resistance of the copper-manganese-nickel-tin-cobalt medium-entropy copper alloy.
[0053] The invention improves the ability of the medium-entropy copper alloy to inhibit the formation of discontinuous precipitation phases by introducing the Co element and combining solid solution treatment and aging treatment. The obtained medium-entropy copper alloy has extremely high hardness and yield strength, and has excellent fracture toughness and wear resistance.
[0054] The present invention also provides the use of the medium-entropy copper alloy described in the above technical scheme or the medium-entropy copper alloy prepared by the preparation method described in the above technical scheme as a wear-resistant material. The wear-resistant material can be used as a sliding part in the fields of aviation, aerospace, energy, engineering machinery, marine equipment, etc.
[0055] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] Cu 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 Preparation of medium entropy copper alloy
[0058] (1) Using Cu metal powder, Mn metal powder, Ni metal powder, Sn metal powder and Co metal powder with impurity content less than 0.1wt% as raw materials, according to Cu 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 The weight percentage of each component of the medium-entropy copper alloy was measured by weighing the metal powders one by one, and then each metal powder was ultrasonically cleaned in anhydrous ethanol for 20 min, and then placed in an oven at 80°C until dry.
[0059] (2) The dried metal powders are placed into a graphite crucible in order of melting point from low to high, and the crucible is placed in a smelting furnace. The furnace chamber is evacuated by a mechanical pump, and then nitrogen is introduced as a protective gas. The evacuation and introduction of the protective atmosphere are repeated three times.
[0060] (3) Starting the heating power supply, first heating the powder mixture to 1300° C. and keeping the temperature for 10 min for melting, then continuing to raise the temperature to 1500° C. and refining for 10 min. After the refining is completed, the mixture is cooled to room temperature with the furnace to obtain an ingot.
[0061] (4) Solution treatment process: The ingot was placed in a resistance furnace and heated from room temperature to 900°C at a heating rate of 10°C / min in an air atmosphere, and kept at this temperature for 4 h. The alloy was then quickly taken out (sample transfer time was 7 s) and placed in room temperature water (25°C) for quenching. After the alloy was cooled to room temperature, it was dried in an oven at 80°C for 30 min.
[0062] (5) Aging treatment process: The alloy obtained by solution treatment was placed in a muffle furnace and heated to 450°C at a heating rate of 10°C / min in an air atmosphere. After being kept at this temperature for 300 min, it was cooled to room temperature in the furnace to obtain Cu 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 Medium-entropy copper alloy.
[0063] Example 2
[0064] The medium-entropy copper alloy was prepared according to the method of Example 1, except that the composition of the medium-entropy copper alloy was Cu 45 Mn 8 Ni 35 Sn 7 Co 5 , the smelting temperature is 1200℃.
[0065] Example 3
[0066] The medium-entropy copper alloy was prepared according to the method of Example 1, except that the composition of the medium-entropy copper alloy was Cu 45 Mn 8 Ni 30 Sn 7 Co 10 .
[0067] The phase composition of the medium entropy copper alloy prepared in Examples 1 to 3 was analyzed by X-ray diffractometer (XRD), and the obtained XRD spectra are as follows: Figure 1 , 4 7; The medium entropy copper alloy prepared in Examples 1 to 3 was subjected to microstructural examination using a scanning electron microscope (SEM) to obtain a SEM image, as shown in FIG. Figure 2 , 5 8; the Vickers hardness (testing according to GB / T4340.3-2012), yield strength, compressive strength, fracture toughness and wear rate (ASTM G99-17) of the medium entropy copper alloys prepared in Examples 1 to 3 were tested using a Vickers hardness tester, a universal material testing machine and a rotary friction and wear testing machine. The results are listed in Table 1. The obtained compressive mechanical properties (GB / T 7314-2017) are as follows Figure 3 , 6 and 9. Among them Figure 1 The Cu prepared in Example 1 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 XRD spectrum of medium entropy copper alloy, Figure 4 The Cu prepared in Example 245 Mn 8 Ni 35 Sn 7 Co 5 XRD spectrum of medium entropy copper alloy, Figure 7 The Cu prepared in Example 3 45 Mn 8 Ni 30 Sn 7 Co 10 XRD spectrum of medium entropy copper alloy; Figure 2 The Cu prepared in Example 1 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 SEM image of medium entropy copper alloy, Figure 5 The Cu prepared in Example 2 45 Mn 8 Ni 35 Sn 7 Co 5 SEM image of medium entropy copper alloy, Figure 8 The Cu prepared in Example 3 45 Mn 8 Ni 30 Sn 7 Co 10 SEM image of medium entropy copper alloy; Figure 3 The Cu prepared in Example 1 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 Compressive mechanical properties curve of medium entropy copper alloy, Figure 6 The Cu prepared in Example 2 45 Mn 8 Ni 35 Sn 7 Co 5 Compressive mechanical properties curve of medium entropy copper alloy, Fig. 9 The Cu prepared in Example 3 45 Mn 8 Ni 30 Sn 7 Co 10 Compressive mechanical property curve of medium entropy copper alloy.
[0068] Table 1 Mechanical properties of medium entropy copper alloys prepared in Examples 1 to 3
[0069]
[0070] Depend on Figure 1 , 4It can be seen from Figure 7 that the medium entropy copper alloy provided by the present invention is composed of A1 phase, B1 phase and H-L1 phase. 2 The heat treated Cu phase structure was analyzed by scanning electron microscopy (SEM). 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 Microstructure of medium-entropy copper alloy.
[0071] Depend on Figure 2 Visible Cu 45 Mn 8 Ni 37.5 Sn 7 Co 2.5 Medium H-L1 2 The phase is evenly distributed in the matrix in a granular state. Figure 5 and Figure 2 It can be seen that due to the increase of Co content in the alloy, Cu 45 Mn 8 Ni 35 Sn 7 Co 5 Medium granular H-L1 2 The precipitation of the phase is suppressed by Figure 8 It can be seen that Cu 45 Mn 8 Ni 30 Sn 7 Co 10 Medium H-L1 2 The phase is continuously and evenly distributed in the matrix.
[0072] Combining Table 1 and Figure 3 , 6 It can be seen from Figures 9 and 10 that the medium-entropy copper alloy provided by the present invention has both high mechanical properties and good wear resistance.
[0073] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A medium entropy copper alloy, characterized in that The following atomic percentages of elements are included:
2. The medium entropy copper alloy according to claim 1, characterized in that: The microstructure of the medium-entropy copper alloy includes an A1 phase, a B1 phase and an H-L12 phase.
3. The medium entropy copper alloy according to claim 2, characterized in that: The volume percentage of the H-L12 phase is 5 to 18%.
4. The method for preparing the medium-entropy copper alloy according to any one of claims 1 to 3, comprising the following steps: The materials are mixed according to the element ratio and then smelted, and the molten alloy obtained by smelting is cooled to obtain an ingot; The ingot is subjected to solution treatment and aging treatment in sequence to obtain the medium-entropy copper alloy.
5. The preparation method according to claim 4, characterized in that: The temperature of the solution treatment is 780-900° C. and the time is 3-6 hours.
6. The preparation method according to claim 5, characterized in that: The heating rate to the temperature required for the solution treatment is 10-12°C / min.
7. The preparation method according to claim 4, characterized in that: The aging treatment is carried out at a temperature of 400 to 550° C. and for a time of 3 to 5 hours.
8. The preparation method according to claim 7, characterized in that: The heating rate to the temperature required for the aging treatment is 5 to 12°C / min.
9. The preparation method according to claim 4, characterized in that: The smelting includes vacuum induction melting or suspension melting; The smelting temperature is 1200-1550° C. and the smelting time is 10-30 minutes.
10. Use of the medium-entropy copper alloy according to any one of claims 1 to 3 or the medium-entropy copper alloy prepared by the preparation method according to any one of claims 4 to 9 as a wear-resistant material.